Normalisasi Praktik Flexploitation dan Kerentanan Jurnalis Daring di Yogyakarta - Elizabeth F. Warikar (Jurnal Ilmu Komunikasi)
This research describes the social, economic, and political factors in the digital media ecosystem, which cause the normalization of flexploitation practices among journalists in Yogyakarta. This phenomenological research uses literature study, observation, and in-depth interviews to collect primary data. The findings of this research show that the schemes of news organizations in Yogyakarta are still slow in adapting to the technological revolution, the illusion of increasing flexibility, and the impact of the New Order era. There needs to be government intervention, the Press Council, and collaboration between journalist organizations, labor unions, and educational institutions as mitigation efforts.